RNA damage: the forgotten target of clinical compounds - Simms, Nicole; Knight, John R. P. (Frontiers in RNA Research, 2023)
Unlike DNA, RNA can be found in every sub-cellular compartment, where it is used to impart the genetic code or perform essential catalytic activities. As a result, damage to RNA is more spatially pervasive than damage to DNA and can have profound effects on gene expression and RNA-dependent activities. The past decade has seen the pathways involved in detecting and responding to damage of specific RNAs defined. These studies largely used high concentrations of tool compounds or deletion of essential factors for the response to RNA damage to study its effects. RNA is damaged by both endogenous and exogenous agents, with the effect of exogenous agents administered as therapeutics the focus of this review. In an effort to formalise studies into clinical RNA damage biology we propose 4 types of RNA damaging drug that we divide into 2 broad classes. Class 1 drugs result from synthesis using non-canonical nucleotides, which are incorporated into RNA in place of the canonical nucleotides. This class is subdivided depending on the outcome of this misincorporation on the nascent transcript. Class 2 drugs result in covalent ligation of moieties that alter RNA structure. This class is subdivided according to the functionality of the covalent ligation – class 2a are monovalent while class 2b are divalent. We discuss the evidence for and mechanisms of RNA damage as well as highlighting the unknown factors that require further investigation to determine the molecular mechanisms of these drugs.